2012
DOI: 10.1163/138855411x584115
|View full text |Cite
|
Sign up to set email alerts
|

Development of Caenorhabditis elegans dauer larvae in growing populations

Abstract: For species that rely on ephemeral resources, genotype fitness will depend on traits that affect both population growth rates and dispersal. Understanding how such traits are related is central to understanding how they may evolve. Natural populations of Caenorhabditis elegans exhibit rapid population growth within resource-rich patches of decaying organic material and subsequent dispersal, primarily as developmentally-arrested dauer larvae, between patches. The properties of growing populations of C. elegans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…To further investigate this, we determined the number of dauer larvae present a week after food exhaustion, a situation known to increase the number of dauer larvae in N2 [29] . In this assay, analysis of N2 and CB4856 at food exhaustion indicated that only very few dauer larvae had formed at this point (mean ± SE of 12.5±3.66 in N2, with no dauer larvae observed in CB4856, n = 8 for both).…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate this, we determined the number of dauer larvae present a week after food exhaustion, a situation known to increase the number of dauer larvae in N2 [29] . In this assay, analysis of N2 and CB4856 at food exhaustion indicated that only very few dauer larvae had formed at this point (mean ± SE of 12.5±3.66 in N2, with no dauer larvae observed in CB4856, n = 8 for both).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, in the pine forest soil bacterial-feeding nematodes with CP 2-5 increased almost three times more than in the farm soil. The occurrence of dauers is a product of food ex haustion (Green & Harvey, 2012) and they may appear as soon as 2 days after organic matter addition into the soil (Zelenev et al, 2004). Incorporation of N-rich plant biomass into the soil induce dauer formation (van Eekeren et al, 2009).…”
Section: Re L a T Io N Sh Ip B E T W E E N P H Y S Ic O -C H E M Ic Amentioning
confidence: 99%
“…Population assays were performed as described by Green and Harvey (2012), except that agar concentration was varied, with normal, dauer agar, plates containing 20 g l À1 and sloppy agar plates containing 4 g l À1 . This corrected an initial issue with the population assays where the wild isolates tended to burrow into the agar, making recovery and counting impossible.…”
Section: Assaysmentioning
confidence: 99%
“…For the analyses of the wild isolates and of the ILs, populations were initiated with 100 ml of a 20% (wv À1 ) suspension of E. coli in water and monitored daily until food exhaustion, when the population size and the number of dauer larvae were determined as described by Green and Harvey (2012). Wild isolates were analysed in two experimental blocks with an N2 control in each block and 10 plates per isolate.…”
Section: Assaysmentioning
confidence: 99%
See 1 more Smart Citation